On the existence of solutions for Volterra integral inclusions in Banach spaces. (1993) - Avgerinos Avgerinos, Evgenios P. Evgenios P.
Abstract : In this paper we examine a class of nonlinear integral inclusions defined in a separable Banach space. For this class of inclusions of Volterra type we establish two existence results, one for inclusions with a convex-valued orientor field and the other for inclusions with nonconvex-valued orientor field. We present conditions guaranteeing that the multivalued map that represents the right-hand side of the inclusion is α -condensing using for the proof of our results a known fixed point theorem for α -condensing maps.